ANALISIS FAKTOR-FAKTOR PENGHAMBAT REALISASI KANTIN SEHAT DI SDN KEMAYORAN 2 BANGKALAN - Rohmah, Dewi; Erika Zakiah Sholiha; Keisha Najwa Aqilah; Robiatul Adawiyah; Sintia Febriyanti; Ahmad Sudi Pratikno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify and examine various barriers to the implementation of the healthy cafeteria program at SDN Kemayoran 2 Bangkalan. Using a descriptive qualitative method, data were collected through in-depth interviews, direct observation, and document analysis. The informants involved included three teachers, twelve upper-grade students (grades 4, 5, and 6), and three canteen vendors. Data analysis was conducted interactively using the Miles and Huberman model. The results revealed four factors hindering the realization of a healthy canteen: (1) students’ strong sensory preference for flavor (MSG), (2) the dilemma of reduced income for canteen vendors if healthy canteen regulations are implemented, (3) vendors shifting their sales strategies toward less healthy snacks because students’ primary food needs are met by the Free Nutritious Meals (FNM) program, and (4) the weakening consistency of the school’s control and supervision system. Consequently, the “Healthy Cafeteria” label risks becoming nothing more than a mere formality without proper planning. This study hopes that schools will not only monitor but also act as facilitators by providing concrete solutions, such as training in developing healthy and cost-effective menus.